Clot length predicts recanalisation but not outcome after basilar artery occlusion - van der Hoeven, Erik JRJ (Eur Stroke J, 2016)
INTRODUCTION: The aim of our study was to evaluate the effect of clot length on both recanalisation and outcome in acute basilar artery occlusion (BAO). PATIENTS AND METHODS: One hundred forty-nine patients with an acute basilar artery occlusion from the Basilar Artery International Cooperation Study (BASICS) were included. Clot length was assessed on computed tomographic angiography. Thrombus length was divided in tertiles and was related to recanalisation and outcome at 1 month, with Poisson regression. Modified Rankin scale scores of 4 or 5, or death were considered poor outcomes. Additionally, clot length was analysed as a continuous variable. RESULTS: Forty-nine patients (33%) had a short (4–11 mm), 50 (34%) an intermediate (12–22 mm), and 50 (34%) a long clot (≥23 mm). Multivariable analyses showed a significantly lower probability of recanalisation but no statistically significant difference in poor outcome for patients with a long clot compared with patients with a short clot (RR 0.64, 95% CI: 0.42–0.98 and RR 1.10, 95% CI: 0.88–1.37, respectively). No statistically significant differences were found for patients with an intermediate clot length compared with patients with a short clot length (RR 0.97, 95% CI: 0.75–1.25 and RR 1.11, 95% CI: 0.88–1.40, respectively). Analyses of clot length as a continuous variable showed a 10% reduction in chance of recanalisation and a 2% increase in risk of poor outcome with every centimeter increase in clot length (RR 0.90, 95% CI: 0.78–1.04 and RR 1.02, 95% CI: 0.98–1.05, respectively). CONCLUSIONS: Clot length predicted recanalisation but not outcome at 1 month in patients with a BAO. We found 2% more poor outcome and 10% less recanalisation with every centimeter increase in clot length.